2003
DOI: 10.1002/bit.10885
|View full text |Cite
|
Sign up to set email alerts
|

On‐line monitoring of important organoleptic methyl‐branched aldehydes during batch fermentation of starter culture Staphylococcus xylosus reveal new insight into their production in a model fermentation

Abstract: A small fermentor (55 mL) was directly interfaced to a membrane inlet mass spectrometer for continuous on-line monitoring of oxygen and volatile metabolites during batch fermentations of the starter culture Staphylococcus xylosus. Using this technique, we were able to correlate production of the very important flavor compounds 2-methylbutanal, 3-methylbutanal, and 2-methylpropanal with various growth conditions. We found that the aldehydes were present in the culture broth only as transient metabolites. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In support of the observations shown in Fig. 4, the observations of de Vos Petersen et al (2004) indicate that some portion of the transport behavior of PDMS membranes is proportional to analyte fugacity rather than to analyte concentration.…”
Section: Mims Dic Linearity Experimentssupporting
confidence: 76%
See 1 more Smart Citation
“…In support of the observations shown in Fig. 4, the observations of de Vos Petersen et al (2004) indicate that some portion of the transport behavior of PDMS membranes is proportional to analyte fugacity rather than to analyte concentration.…”
Section: Mims Dic Linearity Experimentssupporting
confidence: 76%
“…4 suggest that gas transport through PDMS membranes may be more complicated than has been previously supposed. Further, the work of de Vos Petersen et al (2004) showed that salinity exerted a strong influence on ln ln black. Ion currents against salinity are presented in red (1.27 atm absolute) and blue (184 atm absolute).…”
Section: Mims Dic Linearity Experimentsmentioning
confidence: 96%
“…They are used as aroma producers in the production of fermented meat products [7]. During the fermentation process they convert the BCAAs valine, leucine, and isoleucine into flavour important BC aldehydes and short chain carboxylic acids [8,9]. The production of these metabolites is closely linked to the biosynthesis of cellular BCFAs [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…On‐line high‐performance‐liquid‐chromatography, and on‐line mass spectrometry are examples of more expensive stand‐alone instruments with capacity to provide on‐line data for proteins, metabolites or other low‐molecular weight compounds. These methods are more costly to set up in combination with soft sensors, they require significant support and operator surveillance, but could, in many cases, supply reliable and valuable process data with short duration.…”
Section: ‘Hardware Sensor’ Alternativesmentioning
confidence: 99%